Workplace Romance 2.0: Developing a Communication Ethics Model to Address Potential Sexual Harassment from Inappropriate Social Media Contacts Between Coworkers - Mainiero, Lisa A.; Jones, Kevin J. (2013)
This article examines ethical implications from workplace romances that may subsequently turn into sexual harassment through the use of social media technologies, such as YouTube, Facebook, LinkedIn, Twitter, text messaging, IMing, and other forms of digital communication between office colleagues. We examine common ethical models such as Jones (Acad Manag Rev 16:366–395, 1991) issue-contingent decision-making model, Rest’s (Moral development: Advances in research and theory, 1986) Stages of Ethical Decision-Making model, and Pierce and Aguinis’s (J Org Behav 26(6):727–732,2005) review of workplace romance versus sexual harassment issues. The article makes a contribution by developing a new communication ethics model that includes response positive and response negative contingencies to guide decision-making about inappropriate social media contacts that spillover into the workplace. In addition, we recommend that human resource personnel take a more active role in communicating appropriate ethical rules of conduct concerning the use of social media technologies inside and outside the office.
Keywords: workplace romance; Tumblr; Twitter; Social media technologies; Sexual Harassment; office romance; LinkedIn; Human resource guidelines; Human resource codes of conduct; Facebook; Communication ethics; Business Ethics